2019
DOI: 10.9745/ghsp-d-19-00157
|View full text |Cite
|
Sign up to set email alerts
|

Using Data to Keep Vaccines Cold in Kenya: Remote Temperature Monitoring With Data Review Teams for Vaccine Management

Abstract: Using technology to make data visible to stakeholders and giving those stakeholders a framework for analyzing that data for decision making improves cold chain management of vaccines in Kenya.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
(9 reference statements)
1
4
0
1
Order By: Relevance
“…In terms of documentation of twice-daily manual temperature records, it was observed that tools were not consistent in completing them and this was comparable to findings from the study conducted by Lutukai et al [ 30 ]. Not only understaffing and unavailability of a functional temperature monitoring tool may be possible, but also the unavailability of a temperature recording chart was observed.…”
Section: Discussionsupporting
confidence: 83%
“…In terms of documentation of twice-daily manual temperature records, it was observed that tools were not consistent in completing them and this was comparable to findings from the study conducted by Lutukai et al [ 30 ]. Not only understaffing and unavailability of a functional temperature monitoring tool may be possible, but also the unavailability of a temperature recording chart was observed.…”
Section: Discussionsupporting
confidence: 83%
“…Various studies in Africa and other parts of the world identified weaknesses in cold chain management that influence vaccine wastages, including shared knowledge among health providers, breakdown of the cold chain systems, power interruption, and quality of refrigerators [9,[32][33][34]. In this study, the vaccine wastage level was lower than those reported in other studies conducted in India, which reported a wastage of DTP and MR to be 32.1% and 32.2%, and 25.4%, and 21.7%, for Kangra and Pune districts, respectively [35].…”
Section: Discussionmentioning
confidence: 99%
“…Mercy Lutukai, Elizabeth A Bunde, Benjamin Hatch, Zoya Mohamed, Shahrzad Yavari , Ernest Some , Amos Chweya , Caroline Kania , Jesse C Ross , Carmit Keddem , Yasmin Chandani (2019) said that Monovalent live Rotavirus vaccine (RV1) is given orally in two doses a minimum 4 weeks apart. It is provided as a lyophilized powder that is reconstituted just before administration.…”
Section: Practices By Health Work In Rotavirus Preventionmentioning
confidence: 99%